University-industry collaboration, innovation capability and firm performance in Brazil : the role of resources and channels - Mikhailov, Andrei (2023)
The university-industry (U-I) collaboration is an essential factor for industrial innovation. The investigation of UIC outcomes from the firms’ perspective has attracted scholars’ attention in the last few years. Firms that collaborate with universities may benefit from access to valuable resources, such as access to state-of-art scientific knowledge and human resources, patents, new methods, and university infrastructure and technical equipment. In turn, access to resources is vital for building innovation capability, which is essential for innovation performance. However, the studies that analyzed the benefits of U-I collaboration for the firms underexplored the capabilities issue. Hence, the following research question is proposed: which are the most benefic universities’ resources and U-I collaboration channels to the innovation capability and performance of manufacturing firms? In 2021, the researcher applied a survey with 176 Brazilian industrial firms that collaborated with universities. To measure firms’ innovation capability, it was used Zawislak’s (2012) model. This model splits innovation capability into four capabilities: management, transactions, operations, and development. The data was analyzed through the structural equation modeling (SEM) and multiple regression techniques. The results showed that the use of universities’ resources for product and process innovation based on knowledge infrastructure is more benefic for firms’ innovation capability and performances than applied science. Specifically, the use of research results, laboratories and physical infrastructure, new designs and instruments and equipment are the most benefic resource types for innovation capability. In turn, the use of U-I collaboration channels based on knowledge transfer to conduct firms’ innovation activities is more benefic for innovation capability and performance than innovation networks. Specifically, technology licensing, publications and reports, and training, are among the most benefic U-I collaboration channels for improving firms’ innovation capability. The contributions of the present dissertation are two-fold. First, the present study contributes to the literature by analyzing the impact of U-I collaboration on firm innovation capability and performance within a holistic approach. In this sense, it combines the measuring of the influence of the use of different universities’ resources and U-I collaboration channels on the firms. 2 Second, the study contributes to the literature by suggesting options for improving firms’ innovation capability.